Effect of Brönsted acidic ionic liquid 1‐(1‐propylsulfonic)‐3‐methylimidazolium chloride on growth and co‐fermentation of glucose, xylose and arabinose by Zymomonas mobilis AX101. (16th April 2018) - Gyamerah, M.; Ampaw‐Asiedu, M.; Mackey, J.; Menezes, B.; Woldesenbet, S.
Abstract: The potential of large‐scale lignocellulosic biomass hydrolysis to fermentable sugars using ionic liquids has increased interest in this green chemistry route to fermentation for fuel‐ethanol production. The ionic liquid 1‐(1‐propylsulfonic)‐3‐methylimidazolium chloride compared to other reported ionic liquids has the advantage of hydrolysing lignocellulosic biomass to reducing sugars at catalytic concentrations (≤0·032 mol l −1 ) in a single step. However, effects of this ionic liquid on co‐fermentation of glucose, xylose and arabinose to ethanol by recombinant Zymomonas mobilis AX101 has not been studied. Authentic glucose, xylose and arabinose were used to formulate fermentation media at varying catalytic 1‐(1‐propylsulfonic)‐3‐methylimidazolium chloride concentrations for batch co‐fermentation of the sugars using Z . mobilis AX101. The results showed that at 0·008, 0·016 and 0·032 mol l −1 ionic liquid in the culture medium, cell growth decreased by 10, 27 and 67% respectively compared to the control. Ethanol yields were 62·6, 61·8, 50·5 and 23·1% for the control, 0·008, 0·016 and 0·032 mol l −1 ionic liquid respectively. The results indicate that lignocellulosic biomass hydrolysed using 0·008 mol l −1 of 1‐(1‐propylsulfonic)‐3‐methylimidazolium chloride would eliminate an additional separation step and provide a ready to use fermentation substrate. Significance and Impact of Study: This is the first reported study of the effect of the Brönsted acidic ionic liquid 1‐(1‐propylsulfonic)‐3‐methylimidazolium chloride on growth and co‐fermentation of glucose, xylose and arabinose by Zymomonas mobilis AX101 in batch culture. Growth on and co‐fermentation of the sugars by Z . mobilis AX 101 with no significant inhibition by the ionic liquid at the same catalytic amounts of 0·008 mol l −1 used to hydrolyse lignocellulosic biomass to reducing sugars overcome two major hurdles that adversely affect the process economics of large‐scale industrial cellulosic fuel ethanol production; the energy‐intensive hydrolysis and ionic liquid separation steps. Abstract : Significance and Impact of Study: This is the first reported study of the effect of the Brönsted acidic ionic liquid 1‐(1‐propylsulfonic)‐3‐methylimidazolium chloride on growth and co‐fermentation of glucose, xylose and arabinose by Zymomonas mobilis AX101 in batch culture. Growth on and co‐fermentation of the sugars by Z . mobilis AX 101 with no significant inhibition by the ionic liquid at the same catalytic amounts of 0·008 mol l −1 used to hydrolyse lignocellulosic biomass to reducing sugars overcome two major hurdles that adversely affect the process economics of large‐scale industrial cellulosic fuel ethanol production; the energy‐intensive hydrolysis and ionic liquid separation steps.